A New Experimental Allergic Rhinitis Model in Mice - Şükran Köse; Tuba Tatlı Kış; Gülden Diniz; Ilkay Akbulut; Başak Göl Serin; Canberk Yılmaz; Mine Özyazıcı; Mesut Arıcı; Aysu Yurdasiper; Osman Yılmaz (Galenos Publishing House, 2021)
Objective: Allergic rhinitis (AR) is an inflammatory disease of the nasal mucosa mediated by IgE after exposure to an allergen. The most well known related comorbidity of AR is asthma. This study was planned due to the need for an animal model for studies on AR-asthma coexistence. In this study, the frequency of AR accompanying in the asthma model created in mice,and the usability of the related model in AR studies will be investigated. Methods: In our study, 6-8 week-old, 18-20 g BALB/c mice were used. Chicken egg ovalbumin (OVA Grade V, Sigma) was administered through intraperitoneal (IP) route at doses of 10 μg on days 0 and 14. Mice were exposed to aerosolized 2.5% ovalbumin solution in sterile saline for 30 minutes 3 days a week for 8 weeks, starting 7 days after the last IP administration (21st day). After exposure to OVA, mice were observed for typical signs of AR including sneezing, runny nose, and nasal itching. The final diagnosis of AR was made by histopathological examination of the rhinotracheal tissues of mice. Results: In our study, all mice exposed to ovalbumin received histopathologic diagnosis of AR. Increased number of capillaries lymphocytes, polymorphonuclear leukocytes and eosinophilsper square millimetre of rhinotracheal tissues were calculated in the murine model of AR compared to the the control group. Conclusion: This study introduced a new AR model, not cited in the literature, and induced with the longest-term ovalbumin exposure in the literature. It was concluded that this model, known as the asthma model, can also be used to induce an AR model and can be used in studies investigating coexistence of allergic rhinitis and asthma.